Isolation and Characteristics of Corn-Based Cellulolytic Fungi as Fibrous Feed Bioactivators - Meilisa Delfiyana; Yunilas .; Sayed Umar; Nurzainah Ginting; Hasnudi . (Universitas Sumatera Utara, 2018)
Microbes live in nature freely in water, air, or soil. One type of microbe is fungi. Fungi are microorganisms that are able to degrade fiber. This study aims to isolate fungi from corn waste and test the degradation ability of the best corn waste fungi fiber as a fibrous feed bioactivator. This research was carried out at the Laboratory of Animal Production, Faculty of Agriculture, Animal Husbandry Study Program, University of North Sumatra, in March 2018 - June 2018. This study used corn waste (corn cobs, corn straw, corn husk, corn flowers and corn roots). Parameters observed were macroscopic morphology (colony size, colony shape, clony color, colony elevation, colony edge), microscopic morphology (form of hyphae, conidial shape, and conidiophoric surface) and the ability to degrade fiber in fungi. Conclusions from the results of research on corn waste exploration obtained 6 fungi isolates, 4 of which were cellulolytic fungi that were able to degrade fibrous feed, namely two strains of Aspergillus sp., Fusarium sp., And Rizoctonia sp. Isolates which have a potential to degrade fiber are JE isolates (Rizoctonia sp. fungi) with a cellulolytic index of 1,178.